Metabolomic Dynamics Reveals Oxidative Stress in Spongy Tissue Disorder During Ripening of Mangifera indica L. Fruit - Pranjali Oak; Ashish Deshpande; Ashok Giri; Vidya Gupta (Metabolites, 2019)
Spongy tissue disorder, a mesocarp specific malady, severely affects the flavor and pulp characters of Alphonso mango fruit reducing its consumer acceptability. Here, we investigated comparative metabolomic changes that occur during ripening in healthy and spongy tissue-affected fruits using high resolution mass spectrometric analysis. During the spongy tissue formation, 46 metabolites were identified to be differentially accumulated. These putative metabolites belong to various primary and secondary metabolic pathways potentially involved in maintaining the quality of the fruit. Analysis revealed metabolic variations in tricarboxylic acid cycle and gamma amino butyric acid shunt generating reactive oxygen species, which causes stressed conditions inside the mesocarp. Further, reduced levels of antioxidants and enzymes dissipating reactive oxygen species in mesocarp deteriorate the fruit physiology. This oxidative stress all along affects the level of amino acids, sugars and enzymes responsible for flavor generation in the fruit. Our results provide metabolic insights into spongy tissue development in ripening Alphonso mango fruit.